Leadership of The Headmaster in Managing Inclusive Elementary School in Brebes Regency - Toharudin, Moh; Ghufroni, Ghufroni (Educational Management, 2019)
The purpose of this study is to analyze and describe the management of inclusive elementary schools, the principal's strategy in motivating the work of inclusive class teachers, and to describe the exemplary value of principals in inclusive elementary schools. Data collection was done by interview, observation, and documentation. Analysis of research data was done by data reduction, data presentation, and drawing conclusions. Checking the validity of the data through testing the credibility, transferability, dependability, and confirmability. The results of this study were as follows: (1) management of inclusive elementary schools by: planning all inclusive school activities at the beginning of the new school year through meetings with teachers and school committees; division of teacher tasks both basic and additional tasks according to their competence; implementing inclusive school work programs according to plan; monitoring during the implementation of activities and evaluating the work program at the end of the semester; (2) the principal's strategy in motivating the work of inclusive class teachers, namely the principal applying reward and punishment, teaching assignments according to his competence, encouraging teachers to excel, giving trust to subordinates, always two-way communication; (3) the principal values ​​exemplified by the principal are: discipline in working, nurturing subordinates, family, responsibility for assignments, and applying the 3S culture senyum, salam, sapa (smiles, greetings, say hello) to teachers and students. The researchers thank the Directorate of Research and Community Service of the Ministry of Research, Technology and Higher Education for providing grant assistance so that this research can be completed.